The The Implementation of Ethical Journalism Based on Teleological Approach in TVRI Jakarta - Fachry Dwito Akbar; Muhammad Rizky Febrian; Prima Widiastuti (Bahasa Indonesia, 2021)
The article aims to find out how the teleological approach is used by journalists who should, of course, adhere to the journalistic ethics code at TVRI Jakarta. And in the field of journalism is the ethical code of journalism is important?. This research method employs qualitative methods and uses interview instruments with two sources from the TVRI station in Jakarta. The result is that this teleological approach is often used by journalists at TVRI Jakarta in carrying out its duties, and of course, its use should be consistent with a journalistic code of ethics.